This will all be over soon : a memoir - Strong, Cecily, 1984- (Simon & Schuster, 2021)
"A powerful memoir from the Saturday Night Live cast member Cecily Strong about grieving the death of her cousin-and embracing the life-affirming lessons he taught her-amid the coronavirus pandemic"--